2016
DOI: 10.1038/aps.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput-compatible assay to measure the degradation of endogenous Huntingtin proteins

Abstract: Aim:The accumulation of disease-causing proteins is a common hallmark of many neurodegenerative disorders. Measuring the degradation of such proteins using high-throughput-compatible assays is highly desired for the identification of genetic and chemical modulators of degradation. For example, Huntington's disease (HD) is an incurable hereditary neurodegenerative disorder caused by the cytotoxicity of mutant huntingtin protein (mHTT). The high-throughput measurement of mHTT degradation is important in HD drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In addition to targeting the machinery regulating AR polyubiquitination, small molecules targeting AR could also modulate AR polyubiquitination. Androgen was previously reported to suppress AR polyubiquitination 24 and is shown here to suppress AR polyubiquitination in the nucleus. In contrast, the small molecule CPPI is a novel AR antagonist capable of enhancing AR polyubiquitination in the nucleus.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to targeting the machinery regulating AR polyubiquitination, small molecules targeting AR could also modulate AR polyubiquitination. Androgen was previously reported to suppress AR polyubiquitination 24 and is shown here to suppress AR polyubiquitination in the nucleus. In contrast, the small molecule CPPI is a novel AR antagonist capable of enhancing AR polyubiquitination in the nucleus.…”
Section: Discussionsupporting
confidence: 56%
“…A second approach was to pulse-chase exogenous or endogenous AR with the methionine analog homopropargylglycine (HPG) coupled with Click chemistry (24)(25)(26), nucleocytoplasmic fractionation, and Western blot analysis (Fig. 2D).…”
Section: Imported Ar Is Degraded In the Nucleus Following Dht Withdrawalmentioning
confidence: 99%
“…The Click-iT AHA (ℒ-azidohomoalaine) kit (Thermo Fisher Scientific, #C10102) was used and the assay was similar to that previously described 30 , 88 . Briefly, cells were starved with methionine-free media for 1 h prior to adding Click-iT AHA for 12 h (pulse, 50 μM).…”
Section: Methodsmentioning
confidence: 99%
“…The Click-iT AHA labeled proteins were then conjugated with biotin by treatment with biotin-DIBO Alkyne (Thermo Fisher Scientific, #C10412). The biotin conjugated proteins were then pulled-down using streptavidin beads (Pierce, #20349), and the HTT level is determined by HTRF 88 .…”
Section: Methodsmentioning
confidence: 99%
“…In our study demonstrating the concept of ATTEC, we observed increased degradation of mutant HTT protein (mHTT) induced by ATTEC. Thus, we used mHTT as the POI for our modeling, and its half-life has been reported to be around 33~40 hours [13][14][15] . In order to facilitate the math calculation, we estimate the mHTT half-life as 36 hours, 6 times of the half-life of mHTT tethered to autophagosomes.…”
Section: Modeling Assumptionsmentioning
confidence: 99%